A preliminary investigation into the effects of jumping saddle design on rider posture - White, C.; Birkbeck, L. (World Congress of Performance Analysis of Sport IX, 2012)
Rider posture plays a significant role in the oneness of horse and rider (Kang et al., 2010). The correct (balanced, free and supple) seat forms the basis for effective communication with the horse via the application of the aids (Belton, 1997). It is also important for rider safety (Peham et al., 2004). Although posture is known to vary with skill (Schils et al., 1993, Kang et al., 2010), the shape of the saddle seat is thought to influence the position of the rider (Belton, 1997). Manufacturers of more recent close contact saddle designs claim to put the rider in closer contact with the horse, aiding balance via the reduction of bulk between the horse and rider (Devoucoux, 2010). What is not clear however, is whether the change in saddle design has an effect on rider posture. Nine experienced riders took part in this cross over designed study, mean height 1.69m (± 0.08m), mean weight 59.42kg (± 7.42kg). All participants rode the Ride Master Pro 2006 (Racewood Equestrian Simulators, Cheshire, UK). Circular, self-adhesive markers of 3.5cm diameter were placed on each rider at selected anatomical landmarks, in accordance with Schils et al. (1993), Lovett et al. (2004) and Terada et al. (2006). Participants rode in 2 saddles with the same stirrup leathers and stirrups; a single flap modern `close contact` jumping saddle (CC) and a traditional style jump saddle with two saddle flaps (TS). A standardised exercise routine was followed for each subject at halt, walk, sitting trot, seated and forward seat canter. For each saddle, once participants had completed the exercise, stirrup leather length was measured; from buckle to the top of the stirrup iron. Data were captured (240 Hz) using a Casio EXILIM EX-FH100 and footage analysed using Dartfish ProSuite® version 5.0. Data analysis was performed using SPSS version 19. Statistical significance was set at P = 0.05. Individual preferred stirrup length was analysed and it was found that participants rode with significantly longer stirrups (t = -3.124, P = 0.035) in the close contact saddle (mean = 50.66 cm ± 4.27 s.d) than the traditional saddle (mean = 46.10 cm ± 2.60). Absolute angles for hip, knee and ankle were analysed for each gait and no significant differences were identified for ankle or hip in walk, trot and seated canter (P > 0.05) however significant differences were found for the knee in walk (Z = -3.97, P < 0.001), trot (Z= -4.18, P < 0.001) and seated canter (Z = -2.65, P = 0.008), with the CC saddle resulting in smaller knee flexion angles throughout. In forward canter, there was no significant difference in knee or ankle angle (P > 0.05) but a significant difference in hip angle was found (Z= -2.50, P = 0.012). The CC saddle was found to have a median absolute angle of 128.1° compared to the TS saddle (133.3°). The results from this preliminary study are of interest as it would appear that saddle design significantly affects rider posture. Whether the resultant posture has any effect on rider performance is unknown at this stage but this has highlighted areas of research into rider posture and the effect of saddle design that warrant further investigation